Differences in composition and potential function of the bacterial communities of cave- and surface-dwelling Mexican salamanders - Julio César García-Sánchez; Sean M. Rovito (Animal Microbiome)
Abstract Caves are a challenging environment for many organisms to inhabit, and many cave-dwelling animals are endemic to particular cave systems. Microorganisms in caves have been shown to have a high biosynthetic capacity, likely as a result of intense biological interactions to deal with resource scarcity. Although cave salamanders have been studied extensively in other parts of the world, they have received relatively little attention in Mexico. Declines of some cave-dwelling species may be due to outbreaks of fungal disease, and a better understanding of their cutaneous microbiome could help with future conservation efforts in the face of disease outbreaks. We characterized the cutaneous microbiome of 11 cave-dwelling Mexican salamanders and their relatives from surface environments using high-throughput 16S amplicon sequencing. We expected cave salamanders to have a more diverse microbiome containing more bacteria with potential antifungal capacity compared to forest salamanders. We also estimated networks of associations between bacteria to test the hypothesis that there are more positive associations in caves. Finally, we used a bioinformatic approach to see if bacteria in caves potentially have more metabolic pathways associated with microbial communication as a result of more intense biological interactions in caves. Although we do not find higher skin bacterial diversity in caves compared to forests, we do find differences in microbiome composition between environments, more positive associations between bacteria, and a slightly higher number of metabolic pathways associated with microbial communication in caves. Our results provide some support for an impact of the cave environment on the skin microbiome of Mexican salamanders.